Respuesta :
The first thing you should see is that you already have the factored polynomial.
Then we can respond more easily to the questions.
We have then:
x-intercepts:
0 = x2 + 12x + 11
0 = (x + 1) (x + 11)
From here, we conclude:
x = -1
x = -11
y-intercept:
f (0) = (0) 2 + 12 (0) + 11
From here we conclude:
y = 11
Answer:
The x-intercepts are
x = -1
x = -11
The y-intercept is
y = 11
Then we can respond more easily to the questions.
We have then:
x-intercepts:
0 = x2 + 12x + 11
0 = (x + 1) (x + 11)
From here, we conclude:
x = -1
x = -11
y-intercept:
f (0) = (0) 2 + 12 (0) + 11
From here we conclude:
y = 11
Answer:
The x-intercepts are
x = -1
x = -11
The y-intercept is
y = 11
Answer:
the x-intercepts are (-1,0) and (-11,0), the y-intercept is (0,11).